Rejoicing or the torments of religious speech - Latour, Bruno; Rose, Julie (Cambridge, United Kingdom Polity, 2013)
Bruno Latourʹs long term project is to compare the felicity and infelicity conditions of the different values dearest to the heart of those who have "never been modern". According to him, this is the only way to develop an anthropology of the Moderns. After his work on science, on technology and, more recently, on law, this book explores the truth conditions of religious speech acts. Even though there is no question that religion is one of the values that has been intensely cherished in the course of history, itʹs also clear that it has become immensely difficult to tune in to its highly specific mode of enunciation. Every effort to speak in the right key sounds awkward, reactionary, pious or simply empty. Hence the necessity of devising a way of writing that brings to the fore this elusive form of speech to render it audible again. In this highly original book, the author offers a completely different tack on the endless "science and religion" conflict by protecting them both from the confusion with the notion of information. Like The Making of Law, this book is one more attempt at developing this "inquiry on modes of existence" that provides an alternative definition of society. -- Publisher description.
"First published in French as Jublier © Les Empecheurs de penser en rond/ Le Seuil, 2002" -- Title page verso.
Translated from the French.
Keywords: Religion -- Philosophy; Communication -- Religious aspects; Language and languages -- Religious aspects